Distribution and Assessment of Trace Elements Contamination in Sediments of Conceição River Basin, Brazil - Lucas Pereira Leão; Raphael de Vicq Ferreira da Costa; Mariângela Garcia Praça Leite; Hermínio Arias Nalini Júnior; Rita Maria Ferreira Fonseca (Geosciences, 2021)
The Conceição river basin, in Quadrilátero Ferrífero (Iron Quadrangle), Brazil, has a long mining history which dates back to the late 17th century, with large gold and iron mines. These activities may be associated with river sediment contamination by trace elements, which were evaluated in this paper by the enrichment factor (EF) and contamination factor (CF). Potential ecological risks, assessed by combining sediment quality control guidelines (SQCG) and potential ecological risk indexes (Er and RI), are presented. Anomalous values for As (92.5 mg·kg−1), Cd (22.49 mg·kg−1), Cr (2582 mg·kg−1), Cu (65.9 mg·kg−1), Pb (58.6 mg·kg−1) and Zn (133.4 mg·kg−1) are observed. The EF and CF indexes indicate contamination by Cd, Cr, Fe, Mn, Ni and Zn in at least one site, with the highest values for Fe and Mn downstream of the iron mines, and Cr and Ni close to the gold mines. According to the SQGC and Er, As, Cd, Cr, and Ni are the most probable to result in adverse effects on sediment-dwelling organisms in this study. The results of principal component analysis (PCA) indicate distinct lithological units as sources of the analyzed elements, which, associated with the indexes, made it possible for the first time to delimit and classify the high concentrations of some analyzed elements as contamination in the Conceição river basin.